Genetic Predisposition to Chronic Lymphocytic Leukemia Is Mediated by a BMF Super-Enhancer Polymorphism - Kandaswamy, Radhika; Sava, Georgina P.; Speedy, Helen E.; Beà, Sílvia; Martín-Subero, José I.; Studd, James B.; Migliorini, Gabriele; Law, Philip J.; Puente, Xose S.; Martín-García, David; Salaverria, Itziar; Gutiérrez-Abril, Jesús; et al. (Cell reports (Cambridge), 2016)
Chronic lymphocytic leukemia (CLL) is an adult B cell malignancy. Genome-wide association studies show that variation at 15q15.1 influences CLL risk. We deciphered the causal variant at 15q15.1 and the mechanism by which it influences tumorigenesis. We imputed all possible genotypes across the locus and then mapped highly associated SNPs to areas of chromatin accessibility, evolutionary conservation, and transcription factor binding. SNP rs539846 C>A, the most highly associated variant (p = 1.42 × 10−13, odds ratio = 1.35), localizes to a super-enhancer defined by extensive histone H3 lysine 27 acetylation in intron 3 of B cell lymphoma 2 (BCL2)-modifying factor (BMF). The rs539846-A risk allele alters a conserved RELA-binding motif, disrupts RELA binding, and is associated with decreased BMF expression in CLL. These findings are consistent with rs539846 influencing CLL susceptibility through differential RELA binding, with direct modulation of BMF expression impacting on anti-apoptotic BCL2, a hallmark of oncogenic dependency in CLL. [Display omitted] •SNP rs539846 underlies 15q15.1 association with chronic lymphocytic leukemia•rs539846 resides in a B cell super-enhancer, disrupting a conserved RELA-binding site•The rs539846 risk allele (A) reduces enhancer activity and RELA binding in CLL•rs539846-A confers lower BMF expression Kandaswamy et al. find that SNP rs539846 underlies the 15q15.1 chronic lymphocytic leukemia risk locus. Follow-up data demonstrate that rs539846 resides within a transcriptional enhancer and alters RELA binding at a conserved site. The rs539846-A risk allele results in reduced RELA-mediated enhancer activity and lower expression of BCL-2-modifying factor.